2021
DOI: 10.1002/cre2.477
|View full text |Cite
|
Sign up to set email alerts
|

Tumor‐infiltrating FoxP3+ T cells are associated with poor prognosis in oral squamous cell carcinoma

Abstract: Objectives: Squamous cell carcinoma is the most common malignancy in the oral cavity. Moreover, human papillomavirus (HPV) infection has been recently implicated in the onset of oral squamous cell carcinoma (OSCC). Regulatory T cells (Tregs) are Forkhead box P3 (FoxP3) positive and are normally involved in the mechanism by which organisms escape attacks from their own immune system; however, in tumors, these cells are known to suppress antitumor immunity and block the attack against tumors. The present study e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…The subsequent screening step by both title and abstract resulted in 23 studies being included. Full‐text screening of the included studies resulted in 14 being selected for review 1,4,6,17,37,44,49–58 . A flowchart that depicts the screening process is displayed in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The subsequent screening step by both title and abstract resulted in 23 studies being included. Full‐text screening of the included studies resulted in 14 being selected for review 1,4,6,17,37,44,49–58 . A flowchart that depicts the screening process is displayed in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Full‐text screening of the included studies resulted in 14 being selected for review. 1 , 4 , 6 , 17 , 37 , 44 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 A flowchart that depicts the screening process is displayed in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…In another study, patients with high FoxP3 expression presented a worse prognosis than patients with low expression. In the same study, the 5-year survival in HPV-positive and HPV-negative OSCC patients demonstrated a slight difference in the prognosis; however, there was no statistical importance, with a better prognosis identified in HPV-positive patients [ 137 ].…”
Section: Human Papilloma Virus (Hpv)mentioning
confidence: 99%
“…1), whereas the significance of the CD4 + infiltrate remains controversial. In particular, the FoxP3 + Tregs subpopulation, which seems to be involved in the process of immune escape, has been correlated with a better outcome in some studies mainly analyzing oropharyngeal carcinomas,40–44 whereas in others it was significantly associated with poor survival, particularly in tumors arising in the oral cavity 45–47. Thus, relevant differences exist between the different anatomic subsites and between HPV + and HPV − carcinomas.…”
Section: Tumor-infiltrating Lymphocytes (Tils)mentioning
confidence: 99%